(untitled) (International journal of artificial intelligence, 2024)
It is known that some young people may have physical disabilities due to birth injuries or injuries to some of their body parts. In such cases, the arms, legs, and supporting organs are more often damaged. In some cases, moderate growth retardation and underdevelopment of body parts may occur. Children with physical disabilities feel uncomfortable among their healthy peers. Such children face many difficulties in the field of choosing a profession compared to other peers. They will need additional support to succeed in their social and professional lives.